Green Innovation for Sustainable MSMEs Performance - Edwin Karim (International Forum of Researchers and Lecturers, 2025)
This study examines the determinants of green innovation and its impact on sustainable business performance among micro, small, and medium enterprises (MSMEs) in the Bandung Raya region of Indonesia. Specifically, the study analyzes the influence of environmental knowledge and market pressure on green innovation, as well as the effect of green innovation on sustainable performance. A quantitative approach was employed using data from 150 MSMEs, and structural relationships were tested through multiple regression analysis. All measurement instruments demonstrated high reliability (Cronbach’s Alpha 0.89–0.95) and validity (corrected item–total correlation > 0.80). The results reveal that environmental knowledge has the strongest positive and significant effect on green innovation (β = 0.728; p < 0.001), indicating that MSMEs with greater environmental awareness are more likely to adopt eco-friendly innovations. Market pressure also significantly influences green innovation (β = 0.257; p < 0.001), demonstrating the role of consumer expectations, competition, and green product trends in shaping sustainable business practices. Furthermore, green innovation has a very strong and significant impact on sustainable business performance (β = 0.847; p < 0.001), suggesting that eco-friendly practices enhance cost efficiency, customer satisfaction, firm reputation, and environmental outcomes. Overall, the study highlights the importance of combining internal awareness with external pressures to foster green innovation and strengthen sustainability among MSMEs. The findings provide theoretical contributions to green innovation and sustainability frameworks, while offering practical implications for MSMEs, policymakers, and business support institutions.